Analisis Konsep Independensi dan Profesionalisme Majelis Ulama Indonesia terhadap Sertifikasi Jaminan Halal pada Industri Makanan Olahan di Jawa Barat: Analysis of the Concept of Independence and Professionalism of the Indonesian Ulema Council on Halal Guarantee Certification in the Processed Food Industry in West Java - Nurhayani, Neng Yani; Sholeh, Aziz; Zulbaidah, Zulbaidah; Pelita, Bobang Noorisnan; Supriyadi, Dedi (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2023)
The Indonesian Ulema Council should maintain professionalism and independence when providing halal certification to ensure that the needs of Muslim consumers are met in accordance with religious teachings. Objectivity should be prioritized to avoid any subjective evaluations. The purpose of this research was to investigate the mechanism for issuing halal guarantee certification in the Processed Food Industry in West Java. Additionally, the study aimed to examine the application of the principles of independence and professionalism of the Indonesian Ulema Council in issuing Halal Guarantee Certification. The methodology employed in this research involved a qualitative approach through field research. The process for obtaining halal assurance certification starts when the Company provides written confirmation that it intends to implement SJH in accordance with the rules outlined by LPPOM MUI. Independence is not just determined by the organizational structure of an institution; expertise, field data, and appearance must also be considered. The Indonesian Ulema Council's application of the Professionalism principle in granting Halal Guarantee Certification to the food processing industry in West Java is evident in its product assessment methods. The Council has effectively coordinated with LPPOM to carry out the process appropriately and efficiently. Majelis Ulama Indonesia senantiasa dituntut untuk menjunjung profesionalisme dan independensi dalam pemberian penetapan halal agar kebutuhan konsumen muslim dapat tetap terjaga dari hal-hal yang diharamkan menurut ajaran agama. Penelitian dilakukan untuk mengetahui mekanisme penerbitan sertifikasi jaminan halal pada Industri Olahan Makanan di Jawa Barat; serta penerapan prinsip independensi dan profesionalisme Majelis Ulama Indonesia dalam menerbitkan Sertifikasi Jaminan Halal. Penelitian ini merupakan penelitian lapangan (field research) dengan pendekatan kualitatif. Mekanisme penerbitan sertifikasi jaminan halal diawali dengan Perusahaan menyatakan secara tertulis tujuan penerapan SJH di perusahaannya sesuai dengan aturan yang telah digariskan oleh LPPOM MUI. Aspek independensi tidak hanya dilihat dari kemandirian dalam penyelenggaraan suatu lembaga saja, jauh dari itu pertimbangan keahlian, data lapangan dan juga penampilan harus menjadi tolak ukur utama. Penerapan prinsip Profesionalisme Majelis Ulama Indonesia dalam menerbitkan Sertifikasi Jaminan Halal pada industri makanan olahan di Jawa Barat dapat dilihat pada metode pengkajian produk industri olahan makanan. Majelis Ulama Indonesia telah mampu melaksanakan koordinasi yang baik dan tepat dengan memberikan peran ini pada LPPOM.